Preparation of Puréed Foods - Wendy J. Dahl; Jamila R. Lepore (EDIS, 2013)
A puréed food is a food item that has been blended, mixed, or processed into a smooth and uniform texture. Examples of foods with a purée consistency include applesauce, pumpkin pie filling, and hummus. Puréed foods may be necessary for people with chewing and/or swallowing problems. For those requiring a puréed diet, it is important to provide a variety of foods. Almost any food can be puréed. However, some puréed foods may be much more acceptable than others. This 4-page fact sheet was written by Wendy J. Dahl and Jamila R. Lepore and published by the UF Department of Food Science and Human Nutrition, March 2013.